A corrosion-resistant spiral spike material for railway

By adjusting the Si content and proposing a new corrosion performance assessment method, the problem of insufficient elongation of ferrite stainless steel spiral nails after rolling is solved, and the performance of spiral nail materials that meet the Ministry of Railways' standards is achieved, and the new The assessment method improves the life and reliability of the spiral nails and meets the requirements of low cost and safe operation.

CN116445822BActive Publication Date: 2024-12-20NINGBO SHUXIANG NEW MATERIAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310662390.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-06
Publication Date
2024-12-20
Estimated Expiration
2043-06-06

AI Technical Summary

Technical Problem

The existing railway spiral nails are prone to failure in coastal humid and windy environments. The existing technology is difficult to meet the low-cost stainless steel material requirements of the Ministry of Railways Q/CR563-2017 standard, and the conventional low-cost ferrite stainless steel 0Cr13 after rolling The elongation after air cooling is insufficient after breaking, which cannot meet the requirements of mechanical properties and corrosion performance.

Method used

By adjusting the Si content to 1.05 wt%-1.5 wt%, the formation process of high-temperature austenite is controlled to ensure that the complete ferrite structure is formed when the rod is air-cooled after rolling, and the material's after-break elongation is greater than 22%, and a new one is proposed The corrosion performance assessment method of uncoated spiral nails is used to replace the assessment method of painted spiral nails by the Ministry of Railways Q/CR563-2017.

Benefits of technology

It significantly improves the service life of spiral nails, meets the mechanical performance and product performance requirements of the Ministry of Railways Q/CR563-2017 standards, provides low-cost and reliable solutions, and provides guarantees for the safe operation of railways.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116445822B_ABST
    Figure CN116445822B_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant spiral spike material for railways. By increasing the Si content in conventional ferritic stainless steel 0C13 from less than 0.6wt% to a Si content in the range of 1.05wt%-1.5wt%, it can be ensured that a bar is rolled to a diameter of 22mm to obtain a complete ferrite structure, so that the elongation after fracture of the material is greater than 22%, meeting the mechanical property requirements of Q / CR564-2017 of the China Railway Corporation, which is a result that cannot be achieved by any batch of conventional ferritic GB / T24511-2017 (0Cr13) and improved stainless steel thereof. The above experiment proves that the use performance of the ferritic stainless steel spiral spike prepared by the invention is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of railway connecting parts, and in particular relates to a corrosion-resistant spiral spike material for railways. Background Art

[0002] Spiral spikes are one of the important components of railway fastener systems. The product is used in large quantities and is very sensitive to price. Therefore, my country still uses Q235 steel to prepare spiral spikes and solves the anti-corrosion problem by surface painting. Since spiral spikes need to experience vibration fatigue, sand and gravel wear and other effects during service, the paint film will quickly fail. After about two years, the spiral spikes will have serious corrosion problems, which will bring great accident risks to the operation of the railway. It is urgent to study new low-cost spike materials and process technologies.

[0003] The railway standard Q / CR563-2017 corrosion performance test and inspection method is formulated for the quality inspection of Q235 steel painted spiral spike film. This method evaluates the quality of the paint film itself and the painting process. Because this method is too harsh, only austenitic stainless steel with higher corrosion performance than 304L can produce spiral spike products that meet the railway standard Q / CR563-2017 surface rust assessment through polishing and other processes. This makes the material and processing costs of the spiral spikes much higher than the product purchase price, which cannot meet the product cost requirements and cannot be used; and the use of ferritic stainless steel such as GB / T24511-2017 (0Cr13) cannot meet the railway standard Q / CR563-2017 surface rust assessment, material and product performance requirements, and cannot be used.

[0004] In recent years, in order to improve the service life and installation convenience of spiral spikes, three technical approaches have been mainly adopted at home and abroad.

[0005] 1. Structural improvement:

[0006] Chinese patent application number CN202023338698.8 discloses a spiral road spike that prevents rotation and enhances the pull-out resistance of anchoring. An anti-rotation handle is added to the fixed end of an ordinary spiral road spike. After anchoring, the anti-rotation handle is integrated with the anchoring agent, so that the spiral road spike can be firmly stuck in the anchoring agent no matter how many times it is disassembled and assembled, thereby ensuring driving safety.

[0007] Chinese patent application number CN201610837386.0 discloses a 3D printed spiral spike for railway concrete sleepers, which is divided into three parts: an upper part, a middle part, and a lower part; the upper part has a standard thread, and the center of the entity is a cylindrical hollow; the middle part is a short cylindrical boss; the lower part has multiple layers of inverted conical bosses, which are arranged in a trapezoidal shape, and the entity has two ribs symmetrically arranged along the length direction of the spiral spike, and the center of the entity is a truncated cone-shaped hollow; the 3D printed spiral spike has high pull-out strength and can effectively prevent the spiral spike from twisting; the 3D printed spiral spike has a complex structure and cannot be produced by traditional processes. The production process using 3D printing technology is simple and saves materials.

[0008] Chinese patent application number CN202030199392.5 discloses an anti-loosening spiral spike, which can prevent the elastic bar from loosening and the nylon sleeve from loosening and endangering driving safety through its appearance design.

[0009] Chinese patent application number CN200720091811.2 discloses an insulating spiral spike, which comprises a spiral spike and an outer edge fixed insulating layer at the lower part of the spiral spike.

[0010] 2. Improved anti-corrosion performance:

[0011] Chinese patent application number CN202021437834.6 discloses a graphene anti-corrosion spiral spike, in which an anti-corrosion layer consisting of graphene anti-corrosion powder coating is electrostatically sprayed on the outer surface of the spike rod body on the lower side of the second thread, the limit ring, the spike rod body below the limit ring and the first thread, thereby solving the problem that the spiral spike will be corroded by rain or humid air, causing rust on the surface of the spiral spike and loosening of the nut on the spiral spike.

[0012] Chinese patent application number CN201310461464.8 discloses a solvent-free railway spiral spike rust-proof coating and a preparation method thereof. The coating comprises 100 parts by mass of epoxy resin, 30-40 parts by mass of glycidyl ether, 0.5-1 part by mass of polyaniline and 1-2 parts by mass of fumed silica, which are sequentially added into a high-speed disperser for dispersion; then 300-400 parts by mass of aluminum tripolyphosphate, 0.1-1 part by mass of diphenylguanidine chromate and 3-5 parts by mass of nano calcium carbonate are sequentially added into the raw materials dispersed by the high-speed disperser, and the dispersion is continued to obtain a component A raw material mixture; the obtained component A raw material mixture is ground on a sand mill and then discharged; 100 parts by mass of modified aromatic amine are heated, and 4-6 parts by mass of salicylic acid are added, and the mixture is stirred for 1 hour under heat preservation to obtain a component B raw material mixture; the ground component A raw material mixture and the obtained component B raw material mixture are mixed and stirred evenly to obtain a final product.

[0013] Chinese patent application number CN201410122576.5 discloses a process for anti-corrosion treatment of railway spiral spikes. After the spiral spikes are treated with composite anti-corrosion treatment, a double-layer corrosion-resistant compound layer can be obtained on the surface of the parts, so that they have excellent corrosion resistance and stability, low brittleness of the infiltration layer, firm bonding with the substrate, porous surface, easy to form an oil film, and can be further passivated to form a series of products with different pH values, which have the advantages of maintenance-free and long life.

[0014] Chinese patent application number CN03112263.9 discloses a multi-element co-penetration treatment method for Q235A spiral spikes, so that the surface layer of Q235A spiral spikes is composed of iron oxide Fe3O4 and iron nitrogen compound [Fe 2-3 (NC)] has an average thickness of more than 18μm and a surface hardness of HV660-HV834. It has good corrosion resistance and therefore does not require frequent inspections and replacements by railway patrol workers after use. It has a lifespan equivalent to that of the sleepers and can be replaced together with them, saving manpower and material resources, reducing costs, and facilitating promotion and application.

[0015] 3. Application of new materials:

[0016] Chinese patent application number CN201210078860.8 discloses a modified thermosetting ultra-high molecular epoxy resin railway special spiral spike, which is made of 12-18% by weight of modified thermosetting epoxy resin, 4-6% by weight of hyperbranched curing cross-linking agent, 60-86% by weight of fibrous reinforcing material, and 5.5-8.5% by weight of powder reinforcing material additive material. It has good corrosion resistance and weather resistance, high strength, and its performance can reach the standard requirements of low carbon steel (such as the strength requirements of Q235 steel workpieces specified in GB / T700-1988 Q235).

[0017] Chinese patent application number CN201811072807.0 discloses a low-cost corrosion-resistant spiral spike for railways and a preparation process thereof. The material composition weight ratio of the spiral spike includes: C≤0.05wt%, Si≤0.6wt%, Mn is 0.5-1.0wt%, S≤0.025wt%, P≤0.03wt%, Cr is 11.5-15.5wt% and the remainder is Fe. The rod is prepared by cold drawing, abutment, machining, and thread rolling to form a spiral spike. The spiral spike is passivated on the surface to obtain a finished product. It has the advantages of strong corrosion resistance and low cost, and is suitable for mass production and processing.

[0018] Through the analysis of the above patent information and the investigation of actual application, it can be found that the above patents are developed on the premise of meeting the requirements of Q / CR563-2017 of the Ministry of Railways. However, it can be found in the actual use process that although a large number of products currently in service can meet the requirements of this standard, the problem of spiral spike failure still occurs in humid coastal environments, windy and sandy environments, etc.

[0019] In order to increase the service life of spiral spikes, stainless steel is an inevitable choice for spiral spikes. At present, high-alloy austenitic stainless steel, martensitic stainless steel, and relatively low-priced medium-chromium and high-chromium ferritic stainless steel AISI430 (1Crl7), 439 (0Cr17Ti), 435 (0Cr17Nb) with niobium, and 441 (1Cr17TiNb) with titanium and niobium are all too expensive to meet the low-cost requirements.

[0020] Low-chromium ferritic stainless steel mainly includes GB / T24511-2017 (0Cr13) and its improved types 405 (0Crl3A1), 410L (00Crl3) and 3CR12 (00Cr12NiTi). Due to the low Cr content, it cannot meet the mechanical and corrosion performance requirements specified in Q / CR563-2017 of the Ministry of Railways. It is necessary to study new corrosion-resistant materials and assessment methods for non-coated spiral spikes. Summary of the invention

[0021] According to the provisions of the Ministry of Railways Q / CR563-2017 standard, the existing railway spiral spikes can be made of Q235 or other materials with better performance than Q235. The prepared spiral spikes are anti-corrosion treated by surface painting or other surface treatment processes. The corrosion performance test and inspection method are formulated for the quality inspection of the Q235 steel painted spiral spike film. This method assesses the quality of the paint film itself and the painting process. Only austenitic stainless steel with higher corrosion performance than 304L can produce spiral spikes that meet the railway standard Q / CR563-2017 through polishing and other processes; while the use of ferritic stainless steel such as GB / T24511-2017 (0Cr13) cannot meet the railway standard Q / CR563-2017 surface rust assessment, material and product performance requirements, which makes the application of stainless steel materials in a dilemma. In addition, studies have found that in the composition range of conventional low-cost ferritic stainless steel 0Cr13, most of the composition points will form martensite during the air cooling process after rolling, and the material performance cannot meet the performance requirement of elongation after fracture greater than 22%. It is urgent to establish new uncoated spiral spike corrosion, material performance and product acceptance standards as the basis for new material research and product acceptance inspection. Otherwise, no factory will be able to produce bars whose composition meets the standard performance requirements of GB / T24511-2017 (0Cr13) and the standard performance requirements of Q / CR563-2017 of the Ministry of Railways.

[0022] In view of the above problems, the present invention provides a corrosion-resistant spiral spike material for railways. On the basis of GB / T24511-2017 (0Cr13), the material is adjusted to increase Si to 1.05wt%-1.5wt%, S: ≤0.02wt%, P: ≤0.025wt% by technical measures, so that the air cooling process of the bar after rolling can be greater than 22%. The developed spiral spike has a service life several times longer than that of the current Q235 spiral spike, greatly improving the reliability of the railway fastener system, providing reliable guarantee for the safe operation of the railway, and providing a new solution for the low cost of railway spiral spikes.

[0023] At the same time, the present invention proposes a new spiral spike corrosion assessment method to replace the assessment method of the painted spiral spike according to the railway standard Q / CR563-2017, which solves the contradiction that the use performance of the non-coated spiral spike is qualified but the corrosion performance test according to the railway standard Q / CR563-2017 is unqualified. The present invention uses a material weight loss or uniform corrosion assessment method to replace the surface treatment or paint rust spot inspection method specified in the Ministry of Railways Q / CR563-2017, which solves the problem of unqualified assessment of stainless steel spikes after sand blowing, and establishes a standard for weight loss or uniform corrosion of uncoated spikes by sampling conventional Q235 spikes and conducting on-track assessment of spikes made of a railway corrosion-resistant spiral spike material according to the present invention.

[0024] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0025] A corrosion-resistant spiral spike material for railways, wherein the elongation after fracture of the spike is greater than 22%.

[0026] Made from the following raw materials in weight percentage:

[0027] Cr: 12.0wt%-14.0wt%, Si: 1.05wt%-1.5wt%, Mn: ≤0.8wt%, C: ≤0.08wt%, S: ≤0.02wt%, P: ≤0.025wt%, Fe: margin.

[0028] A method for preparing a corrosion-resistant spiral spike for railway, comprising the following preparation steps:

[0029] 1) The above-mentioned railway corrosion-resistant spiral spike material is prepared according to the weight ratio, mixed evenly, melted in an electric arc furnace, desulfurized and dephosphorized to obtain high-carbon molten steel, and then loaded into an AOD furnace for decarburization. When the composition meets the requirements, it is transferred to a tundish for continuous casting to form a rod billet with a diameter of 85 mm;

[0030] Place the 85mm diameter billet on the floor of a walking beam continuous heating furnace. Set the furnace temperature to 1150℃-1200℃. Push it forward every 20 minutes. The heating time in the furnace is 45 minutes. Take out the billet at the outlet. The billet temperature is greater than 1050℃.

[0031] 2) After heating the bar with a diameter of 85 mm obtained in the above step, the bar is sent to a multi-pass rolling mill and rolled into a round bar with a diameter of 22 mm through 5-6 passes, with the final rolling temperature being greater than 850° C., and then cooled to room temperature;

[0032] 3) The rod obtained in the above step is processed by cold drawing, abutment, machining and thread rolling to obtain a corrosion-resistant spiral spike for railway.

[0033] The present invention also relates to a corrosion-resistant spiral railroad spike, which is obtained by adopting the above-mentioned preparation method of the corrosion-resistant spiral railroad spike. The corrosion-resistant spiral railroad spike is rolled and air-cooled to obtain a complete ferrite structure, and the elongation after fracture of the railroad spike is greater than 22%.

[0034] Compared with the prior art, the present invention has the following advantages:

[0035] 1. The corrosion-resistant spiral spike material for railways described in the present invention increases the Si content in GB / T24511-2017 (0Cr13) from less than 1.0wt% to 1.05wt%-1.5wt%, and obtains a complete ferrite structure after rolling and air cooling, so that the elongation after fracture of the material is greater than 22%, which solves the problem that the elongation after fracture of conventional ferritic stainless steel 0C13 after air cooling is less than 22%, and meets the mechanical properties and product performance requirements of spiral spikes specified in the Ministry of Railways Q / CR563-2017 standard.

[0036] 2. The corrosion-resistant spiral spike material for railways described in the present invention controls the formation process of high-temperature austenite by adding Si element, thereby solving the problem of unqualified elongation after breaking of 0Cr13 bars after rolling and cooling. This idea of ​​solving the problem has no method reported in the literature to refer to, and is innovative. In the prior art, there is no idea of ​​improving the composition by inferring experiments based on random selection of 0Cr13 components.

[0037] 3. The present invention also provides a corrosion performance assessment method for uncoated railway spiral spikes, and proposes a new spiral spike corrosion assessment method to replace the assessment method of the railway standard Q / CR563-2017 painted spiral spikes, which solves the contradiction that the uncoated spiral spikes have qualified performance but fail the corrosion performance test according to the railway standard Q / CR563-2017. The developed spiral spikes have a service life several times longer than the current Q235 spiral spikes, greatly improving the reliability of the railway fastener system, providing a reliable guarantee for the safe operation of the railway, and providing a new solution for the low cost of railway spiral spikes. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a diagram showing the results of the spiral road spike prepared in Example 1 of the present invention after four years of use;

[0039] Figure 2 This is a picture showing the results of the existing Q235 steel spiral spikes after four years of use;

[0040] Figure 3 is a diagram showing the state of the spiral road spike prepared in Example 1 of the present invention when weighed after being used for four years;

[0041] Figure 4 This is a diagram showing the state of the existing Q235 steel spiral spike when it was weighed after four years of use. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below by way of examples, but these examples should not be considered as limiting the present invention.

[0043] Example:

[0044] A corrosion-resistant spiral spike material for railways is made of the following raw materials in percentage by weight (see Table 1);

[0045] The above-mentioned method for preparing the corrosion-resistant spiral spike for railway comprises the following steps:

[0046] 1) The above-mentioned railway corrosion-resistant spiral spike material is prepared according to the weight ratio, mixed evenly, melted in an electric arc furnace, desulfurized and dephosphorized to obtain high-carbon molten steel, and then loaded into an AOD furnace for decarburization. When the composition meets the requirements, it is transferred to a tundish for continuous casting to form a rod billet with a diameter of 85 mm;

[0047] Place the 85mm diameter billet on the floor of a walking beam continuous heating furnace. Set the furnace temperature to 1150℃-1200℃. Push it forward every 20 minutes. The heating time in the furnace is 45 minutes. Take out the billet at the outlet. The billet temperature is greater than 1050℃.

[0048] 2) After heating the bar with a diameter of 85 mm obtained in the above step, the bar is sent to a multi-pass rolling mill and rolled into a round bar with a diameter of 22 mm through 5-6 passes, with the final rolling temperature being greater than 850° C., and then cooled to room temperature;

[0049] 3) The rod obtained in the above step is processed by cold drawing, abutment, machining and thread rolling to obtain a corrosion-resistant spiral spike for railway.

[0050] Comparative Example:

[0051] The corrosion-resistant spiral spike material for railway is made of the following raw materials in percentage by weight (see Table 1);

[0052] The preparation method of the above-mentioned corrosion-resistant spiral spike for railway is shown in the examples.

[0053] Experimental example:

[0054] The corrosion-resistant spiral spikes for railway obtained from the embodiments and comparative examples were evaluated:

[0055] The preparation of assessment samples includes on-road assessment samples, corrosion performance samples, and mechanical properties test samples. The on-road assessment samples are made of spiral spikes processed in accordance with the Ministry of Railways Q / CR563-2017 standard. The spiral spikes obtained in the embodiment are not surface treated. The corrosion samples are made of rods with an outer diameter of 18 mm and a length of 30 mm. The mechanical properties are processed according to the sample dimensions specified in the GB / T228-2002 standard.

[0056] Test method:

[0057] The on-track assessment samples were tested in accordance with the Ministry of Railways Q / CR563-2017 standard. The salt spray and sulfur dioxide tests were conducted using the experimental methods specified in the Ministry of Railways Q / CR563-2017. The sample dimensions were: 30 mm in length, 20 mm in width, and 10 mm in thickness. The corrosion test of the spiral spikes obtained in the embodiment was conducted using the GB / T39534-2020 method, and the solution was assessed using the GB / T10125 acetic acid salt spray test method. The mechanical properties of the materials were conducted in accordance with the GB / T228.1 standard.

[0058] Experimental results:

[0059] Now, in combination with specific embodiments, the effects of the present invention are verified by using four aspects: material composition comparison, material mechanical property comparison, product mechanical property comparison, and product corrosion property comparison.

[0060] 1. Comparison of chemical composition of materials

[0061] The four groups of samples used in the embodiments of the present invention are shown in Table 1 below. The materials of the embodiments of the present invention and comparative example 1, the 85mm diameter bar blank is placed on the floor of the walking continuous heating furnace, the furnace temperature is set between 1150℃-1200℃, and it is advanced every 20 minutes. The heating time in the furnace is 45 minutes, and the bar is taken out of the outlet. The bar temperature should be greater than 1050℃, and then the heated 85mm diameter bar is sent to the multi-pass rolling mill and rolled into a round bar with a diameter of 22mm through 5-6 passes. After cooling to room temperature, it is cold drawn, pierced, machined, and rolled to form a spiral spike to obtain a finished product. Comparative example 2 takes a Q235 bar with a diameter of 25mm, and is machined and rolled to form a spiral spike to obtain a finished product.

[0062] Table 1: Chemical composition of examples and comparative examples (weight fraction wt / %)

[0063]

[0064]

[0065] 2. Comparison of mechanical properties of materials

[0066] The bars made of five materials from Examples 1 to 5 and the bars made of six materials from Comparative Examples 1 to 6 were processed into spiral spikes, and processed into 9 groups of data mechanical property samples according to the sample requirements specified in GB / T228.1-2021 "Metallic Material Tensile Test Methods". Three samples of each material were taken for experiment. The data are shown in Table 2 below. In Table 2, R m Indicates tensile strength, Rp 0.2 It represents the stress when the non-proportional elongation is specified to be 0.2%, and A represents the elongation after fracture.

[0067] Table 2: Mechanical properties of spiral spikes with different compositions

[0068]

[0069]

[0070] From Example 1 to Example 5, it can be seen that when the Cr content of the material is 12.35wt%-15.5wt%, the Si content is 1.05wt%-1.5wt%, the C content is 0.06wt%-0.08wt%, and the other elements are within the range specified by the national standard of 0Cr13, the mechanical properties of the material can meet the material tensile strength (R m )≥500Mpa, yield strength≥300Mpa, elongation≥22%;

[0071] Comparative Example 1 The spiral spike made of Q235 steel used in actual products can also meet the mechanical property requirements specified in Q / CR563-2017 of the Ministry of Railways, although the stress (Rp 0.2 ) and elongation after fracture (A) are significantly different from those of the stainless steel materials of Examples 1-5, but Examples 1-5 can meet the performance requirements specified in Q / CR563-2017 of the Ministry of Railways;

[0072] Comparative Examples 2 to 6 are randomly selected within the composition range of the national standard GB / T1220-2007 (0Cr13):

[0073] Cr: 11.5wt%-13.5wt%,

[0074] Si: ≤1.0wt%,

[0075] Mn: ≤1.0wt%,

[0076] C: ≤0.08wt%,

[0077] S: ≤0.04wt%,

[0078] P: ≤0.035wt%,

[0079] Fe: remainder.

[0080] It can be seen from Table 2 that the bars with most components randomly selected cannot meet the requirement of material elongation ≥ 22% specified in the Ministry of Railways / CR563-2017.

[0081] In comparative example 6, in the case of a material with a Cr element content of 15.5wt% and a Si content of 1.0wt%, the requirement of an elongation after fracture ≥ 22% specified in Q / CR563-2017 of the Ministry of Railways can be obtained, but it is impossible to infer the experience of increasing the Si content and adjusting the Si content to what range to ensure an elongation after fracture ≥ 22%.

[0082] 3. Comparison of mechanical properties of spiral road spike products

[0083] The spiral spikes of Examples 1-5 and Comparative Examples 1-6 were tested for load bearing and bending resistance according to the provisions of Q / CR563-2017 of the Ministry of Railways. The mechanical properties comparison results are shown in Table 3:

[0084] Table 3: Mechanical properties of spiral spikes

[0085]

[0086]

[0087] Through the above experiments, it can be found that the spiral spike products of Examples 1-5 and Comparative Examples 1 and 6 can meet the requirements of Q / CR563-2017 of the Ministry of Railways: the spike shall not break after a tensile force of 130KN, the spike shall not break after 45° cold bending, the crack (except the truncated cone part) shall have a depth of less than 1mm, and the threaded part shall not have a crack at a curvature of 4 times the inner diameter, i.e. 64mm.

[0088] However, within the composition range of Comparative Examples 2-5, the spiral spikes processed from the prepared rods do not meet the requirement that the threaded portion should not have cracks at a curvature of 4 times the inner diameter, i.e., 64 mm.

[0089] Although the bars of Comparative Example 6 can obtain the result that meets the product requirements when the Cr and Si elements are at the upper limit of the composition, it is only a few points in the entire composition range, and we cannot infer that 0Cr13 meets the product requirements. Based on the composition of Comparative Example 6, we cannot infer the adjustment range of Cr and Si and formulate a formula with a composition range that meets the conventional production requirements.

[0090] 4. Corrosion performance comparison and standard establishment

[0091] The spiral spikes of Examples 1-5 and Comparative Examples 1-6 were tested for corrosion performance according to the provisions of Q / CR563-2017 of the Ministry of Railways. The corrosion performance is shown in Table 4.

[0092] Table 4: Rust corrosion performance test results

[0093]

[0094]

[0095]

[0096] It can be seen from Table 4 that the rust assessment results of Examples 1-5 and Comparative Examples 2-6 are all greater than Level 5, which cannot meet the requirements of the experimental rust assessment method specified in Q / CR563-2017 of the Ministry of Railways. Since the rust assessment method is formulated for painted spiral spikes, this method mainly assesses the quality of the paint film. Obviously, this method is not suitable for assessing the main material of non-coated spiral spikes.

[0097] To this end, the present invention has developed a new product material corrosion resistance assessment method through comparative experimental analysis and on-road assessment experiments on the original Ministry of Railways Q / CR563-2017 corrosion test method, providing an alternative solution for product acceptance.

[0098] The present invention proposes to adopt the experimental method specified in GB / T39534-2020, the solution adopts the acetic acid salt spray test solution specified in GB / T10125, the corrosion specimen adopts the experimental method of a rod with an outer diameter of 18 mm and a length of 30 mm for experiment, the on-road assessment adopts the spiral spike test of Example 1, Example 2 and Comparative Example 1, the on-road assessment adopts the method of interval sampling, the experimental environment selects the coastal section of Hainan Island, and the on-road assessment results are shown in Table 5.

[0099] Table 5: Weight loss corrosion rate test results (mm / a, mm per year)

[0100]

[0101]

[0102]

[0103]

[0104] As can be seen from Table 5, a rod with an outer diameter of 18 mm and a length of 30 mm is used as the corrosion sample. The sample weight is large, the weight loss of 120h salt spray corrosion and 120h sulfur dioxide corrosion is small, and the experimental results fluctuate greatly. However, the weight loss of acetic acid salt spray test solution is large, and the weighing error is small, which is suitable for the assessment of stainless steel non-painted road spikes.

[0105] The present invention adopts the experimental method specified in GB / T39534-2020, the solution adopts the acetic acid salt spray test solution specified in GB / T10125, and the corrosion specimen adopts the experimental method of a rod with an outer diameter of 18mm and a length of 30mm to conduct material and product assessment experiments. The reliability of the inventive method is determined by comparing it with the 4-year assessment experiment of the coastal section of Hainan Island. The spiral road spikes prepared by the material tested by this method have basically no change in appearance after four years of assessment (see Figure 1 ), while the lower part of the Q235 spiral spike with interval casting showed serious diameter reduction (see Figure 2 );

[0106] The products made of the materials of Example 1 and Example 2 were taken out from the pillow plate and showed little change (see Figure 3 ), while the Q235 spiral spikes sampled at intervals were severely corroded (see Figure 4 ).

[0107] The weighing results of product quality loss show that Q235 spiral spikes meet the corrosion performance rust spot assessment standard requirements specified in Q / CR563-2017 of the Ministry of Railways. After 4 years of assessment, the weight loss is between 3.10g and 8.03. The bearing capacity of the spikes has dropped significantly, seriously affecting the safety of railway operation. The spiral spikes of this patent have a weight loss of between 0.026g and 0.038 after 4 years of assessment, which greatly improves the life of the spiral spikes. Therefore, it is feasible to replace the rust spot corrosion inspection standard of Q / CR564-2017 spikes of China Railway Corporation by using the method of GB / T39534-2020, the acetic acid solution specified in GB / T10125 and the corrosion test sample standard specified in this invention for the corrosion assessment method of materials and products.

[0108] Summarize:

[0109] 1. The present invention improves the Si content in conventional ferritic stainless steel 0C13 from less than 1.0wt% to 1.05wt%-1.5wt%, which can ensure that the bar is rolled to a diameter of 22mm and then air-cooled to obtain a complete ferrite structure, so that the elongation after fracture of the material is greater than 22%, which is a result that conventional ferritic stainless steel 0C13 cannot achieve; technicians in this industry cannot infer from Comparative Examples 2 to Comparative Examples 6 that the present invention can ensure the elongation after fracture ≥ 22% by increasing the Si content and adjusting the Si content to the range of 1.05wt%-1.5wt%, and there is no data report or experience to learn from this result.

[0110] 2. The present invention also provides an assessment method for uncoated ferritic stainless steel spiral spikes. Through comparative experiments with the China Railway Corporation's Q / CR564-2017 test standard for coated spiral spikes and strict 4-year assessment of the Hainan Coastal Railway, it is proved that the method can be used as an assessment method for uncoated spiral spikes to test the quality of spiral spike products, solving the problem that the rust spot assessment of the material spiral spike of the present invention using the China Railway Corporation's Q / CR564-2017 standard is not applicable to uncoated products, providing a new inspection method for the inspection of stainless steel spiral spikes, providing a new inspection method for the research of long-life and low-cost stainless steel spiral spike materials, and laying a technical foundation for new material research.

[0111] The spiral road spikes produced by the material of the present invention have been subjected to on-road assessment experiments. After 4 years of assessment, the material can meet the use requirements, but it is necessary to establish new corrosion, material performance and product acceptance standards for uncoated spiral road spikes as a basis for new material research and product acceptance inspection; the corrosive liquid and sample size used in this method are not limited to the methods specified in this patent, and all methods using weight loss and corrosion rate derived from weight loss are within the scope of the claims of this patent.

[0112] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.

Claims

1. A corrosion-resistant spiral spike material for railways, Features: It is a railway corrosion-resistant spiral spike material with a post-fracture elongation greater than 22%. The railway corrosion-resistant spiral spike is rolled and air-cooled to obtain a complete ferrite structure. The material has a tensile strength of ≥500 Mpa and a yield strength of ≥300 Mpa. It is made of the following raw materials in weight percentage: ; 2. A method for preparing a corrosion-resistant spiral spike for railway according to claim 1, Features: The method comprises the following preparation steps: 1) The following corrosion-resistant spiral spike materials are used for railways: ; Prepare according to the weight ratio, mix evenly, and then melt, desulfurize and dephosphorize in an electric arc furnace to obtain high-carbon molten steel, which is then loaded into an AOD furnace for decarburization. When the composition meets the requirements, it is transferred to a tundish for continuous casting to form a billet with a diameter of 85 mm. Place the 85mm diameter billet on the floor of a walking beam continuous heating furnace. Set the furnace temperature to 1150℃-1200℃. Push it forward every 20 minutes. The heating time in the furnace is 45 minutes. Take out the billet at the outlet. The billet temperature is greater than 1050℃. 2) After heating the 85 mm diameter bar obtained in the above step, the bar is sent to a multi-pass rolling mill and rolled into a 22 mm diameter round bar through 5-6 passes, with the final rolling temperature being greater than 850°C, and then cooled to room temperature; 3) The rod obtained in the above step is processed by cold drawing, abutment, machining and thread rolling to obtain a corrosion-resistant spiral spike for railway.